Proceedings of IGU Regional Conference in Japan 1957, Tokyo, The Organizing Comittee of IGU Regional Conference in Japan and The Sciencie Council of Japan, 1959, 606 p. - M. Z. (1960)
Fil: M. Z.. Universidad Nacional de Cuyo. Facultad de Filosofía y Letras